Methodological Foundation of Searching for Optimal Point in the Life Cycle of Entrepreneurial Organization to Pass on to Self-Regulating Ecosystem - O. Yu. Kirillova; V. V. Kuzin (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
The global crisis resulted in a serious drop in economic activity, which causes the necessity to transform organizational forms of commercial companies. Today researchers and practical experts more and more often are looking for analogues in biological world comparing organizational development mechanisms and the development of life in general. One form of organizational interaction both for studying and for practical application can be the ecosystem with its macro- and micro-surroundings. Economic ecosystems enter our life, develop flexibly and improve their efficiency at the expense of drastic cost cutting and introduction of their mechanisms in cooperation with users. The recent research in the field of economic ecosystems is discrete and mainly theoretical that can hardly characterize practical mechanisms used nowadays. The important aspect of using the ecosystem approach in entrepreneurial organization management implies a sufficient and adequate set of indicators of expediency and opportunity for building the ecosystem, which is discussed in the article.